Comparing the effects of physical activity and cognitive training on cognitive performance, physical fitness, and mental health in 9- to 10-year-old children: a randomized clinical trial - Shanshan Wang; Jingwu Liu (Frontiers in Psychology)
AimThis study aimed to compare the effects of physical activity (PA), cognitive training (CT), and their combination (PA+CT) on cognitive performance, physical fitness, and mental health in children aged 9–10 years using a randomized controlled trial (RCT).MethodsThis RCT assigned 145 children (9.74 ± 0.43 years, 46% girls) into four groups: Con (no intervention), PA (aerobic exercises), CT (cognitive tasks), and PA+CT (combined PA and CT). All interventions were administered four times each week for 12 weeks, with 40-min sessions per intervention. The PA group underwent regular physical activity, the CT group received cognitive training, and the PA+CT group combined both activities. Key anthropometric measurements [including height, weight, and BMI body mass index (BMI)], physical fitness tests (including vital capacity, flexibility quality, speed quality, aerobic performance, and physical coordination), cognitive function assessments (including attention, reaction time, and spatial memory), and mental health evaluations (including anxiety and depression) were conducted before and after the intervention.ResultsThe results demonstrated no significant differences in body composition among the groups (p > 0.05). The results of physical fitness revealed that PA, CT, and PA+CT interventions can significantly improve physical fitness parameters in children (p < 0.05); although CT alone showed no significant impact (p > 0.05). The study found that all cognition and mental health parameters improved significantly in the PA, CT, and PA+CT groups than in the control group (p < 0.05), with the strongest effects in PA+CT.ConclusionThis study demonstrates that structured interventions administered four times each week can differentially improve physical fitness, cognition, and mental health outcomes in school-aged children. The synergistic effects observed in the combined PA+CT group underscore the value of integrating physical and cognitive training into school health programs.